Lived experiences of women leaders regarding their spiritual intelligence and its use in higher educational leadership settings in Malaysia - Ramachandaran, Sharmila Devi (2015)
Spiritual intelligence has been portrayed as an important contributor to enhance the sense of meaning and purpose within a workplace. Despite many studies have been conducted on leadership, however, very little studies have been done on the contribution of infusing spiritual intelligence practices for leadership development towards managing the changing environment. This has resulted in critical gaps to understand the strategies to create an educational atmosphere that maximizes the personal and professional potential of leaders in higher educational settings. In addition, significant gaps also remain, particularly in understanding how spiritual intelligence is experienced and practiced by women leaders from higher educational institutions in Malaysia. In such settings where the number of women leaders continues to grow, women tend to place a high value on the attributes of spiritual intelligence. In order to address the issue, this research gap has been examined to understand the experiences of integrating spiritual intelligence practices within Malaysian higher educational institutions. The main purpose of this study is to understand the experience of women academic leaders concerning their spiritual intelligence and its use within the higher educational institutions leadership. This study was carried out through an in-depth exploration of three research questions. The questions are: (1) how do women academic leaders conceptualize spiritual intelligence? (2) How women leaders use their spiritual intelligence in their academic leadership practices? (3) What is the contribution of the use of spiritual intelligence in their academic leadership practices? A qualitative research methodology and existential phenomenological approach were selected as these approaches have been decided as the most precise approaches for the study of a phenomenon of this nature. Data was gathered and generated from nine successful women academic leaders in Malaysian Research Universities. The data collection methods employed to attain the purpose of the study were primarily in-depth interviews with the participants. Each of the interview session lasted between one to two hours, was tape recorded, transcribed verbatim and analyzed using a hands-on approach. Several other documents have also been utilized for this study, such as resources from library, diaries, journal and also logs. The trustworthiness of the study was ensured through member checks, peer examination and maintenance of audit trail. The finding generated four concepts of spiritual intelligence, namely 1) meaning making, 2) holism 3) being vision and value led 4) religious activities. The finding also revealed four approaches of integrating spiritual intelligence into leadership practices which include 1) creating sense of meaning and purpose within people, 2) empowering employees, 3) Viewing things in larger patterns and understand its relationships and connections by being holistic and 4) cultivating and demonstrate values as part of the organisational culture. The contribution of spiritual intelligence to the leadership practice of women academic leaders that has been discovered from the study include 1) employees inspired by vision, 2) increase the credibility and long-term sustainability of institution, 3) systematic way of managing complexity, 4) heightened moral values and reduced ethical issues and 5) resilience to handle stress. The study concluded that spiritual intelligence is projected to transform the workplace into a more meaningful and purposeful atmosphere by constructing balanced and harmonious relationship within employees. Women leaders believe that spiritual intelligence is an effective tool for leaders to manage their institutions in an effective way, specifically within the challenging and high demand working environment. In addition, the integration of spiritual intelligence that brings people together towards mutual understanding and enhance good relationship will undeniably sustain an environment of less stress and burden, as well as conflicts. Conveying the qualities of spiritual intelligence within leadership practices will transform people and also the institution, as well as enhance long-term sustainability. Consequently having enthusiastic and high performance employees will increase the productivity of the institution, which then will lead to the sustainability of the institution. The study has provided valuable insight that will be beneficial for leaders towards managing effectively within the contemporary organization provided with unique skills and attributes.